Biological Disasters in present Prespectives - Archana (SCHOOL SCIENCE, 2018)
Biological disasters are organic origin, including pathogenic microorganism, toxins and bioactive substances. In recent years, biological disasters have become a serious problem for health, environment, and national security. These disasters are of organic origin and can include pathogenic microorganisms, toxins, and bioactive substances. Biological disasters can take the form of an epidemic or pandemic level and can be caused by diseases such as plague, cholera, H1N1 (Swine Flu), and influenza outbreaks. The Center for Disease Control (CDC) has categorized biological Disaster into four biosafety levels (BSL 1-4) to help manage the risks associated with handling biological materials. It is essential to improve the current understanding of health hazards caused by biological disasters. Preventing and preparing for biological disasters requires assessing the risks, medical and public health consequences, medical countermeasures, and longterm strategies. Environmental monitoring can help substantially in preventing outbreaks of waterborne, airborne, vector-borne, and zoonotic diseases. Personal protective equipment like masks, gloves, protective clothing, eye shields, face shields, and shoe covers can help eliminate the source of contamination. Individuals can take steps to prevent disease by eating nutritious balanced food, maintaining up-to-date immunization status, preventing overcrowding, maintaining good ventilation, and protecting themselves from hot and cold weather. Medical treatment for biological disasters may focus on both non-Pharmaceutical and Pharmaceutical approaches. To prevent and control biological disaster, it is crucial to develop capacities, strengthen the existing legislative/regulatory framework, provide mental health support, offer rehabilitation and specialized healthcare, and establish laboratory facilities. Being vigilant and taking proactive measures can help prevent and control biological disasters.